Studi Perbandingan Penguatan Paduan Al-Mg-0,5Si Melalui Perlakuan Panas T6, T5, dan T8 untuk Aplikasi Body Kendaraan Taktis - Absaralita Sabarati; Teguh Budiyanto; Venty Lestari; Muhammad Pasha Arrighi Effendi; Ariq Fakhri; Fauzan Hasan; Bondan T. Sofyan (UM Purwokerto Press, 2026)
Tactical vehicle bodies require materials with high strength, lightweight properties, and resistance to extreme conditions. This study examined the effects of homogenization, deformation, and artificial ageing on the microstructure, hardness, and potential application of Al-Mg-0.5Si (wt.%) alloy as a tactical vehicle body material. Four different treatments were applied: cold deformation + annealing, T6 (precipitation), T5 (hot deformation + precipitation), and T8 (cold deformation + precipitation). The results showed that homogenization at 400 °C for 4 hours increased the secondary dendrite arm spacing (SDAS) by 13–18% and reduced hardness from 54.6–60.7 HRE (as-cast) to 43.2–53.4 HRE (as-homo). After quenching (as-quenched), the highest hardness was observed in the T5 treatment at 98.5 HRE, followed by T8 (87.6 HRE) and T6 (71.8 HRE). Under peak aging conditions, T5 treatment achieved the highest hardness of 51.16 HRB after 18 hours of aging at 180 °C, while T6 and T8 reached 45.98 HRB and 44.6 HRB, respectively. These differences were attributed to a combination of strengthening mechanisms: strain hardening, grain boundary strengthening, and precipitation hardening, with Mg?Si as the primary precipitate. The Al-Mg-0.5Si alloy with T5 treatment exhibited a higher specific hardness compared to HSLA steel, 18.9 versus 8.5, respectively. With superior mechanical properties and a lighter weight, this alloy showed great potential as a tactical vehicle body material. However, additional tests, such as ballistic and dynamic deformation tests, are necessary for further validation.